A novel G·G·T non-conventional intramolecular triplex formed by the double repeat sequence of Chlamydomonas telomeric DNA. Issue 25 (26th May 2022) - Bansal, Aparna; Phogat, Priyanka; Kukreti, Shrikant
Abstract : The competition among the DNA non-canonical structures has been widely studied in repetitive DNA sequences. The Chlamydomonas reinhardtii telomere (TTTTAGGG) n is found an exception to the general idea of forming folded G-quadruplex by few repeats of any telomeric sequence. Abstract : Competition among DNA non-canonical structures has been widely studied in repetitive DNA sequences. The factors affecting DNA structural polymorphism have always been an important area of research. The Chlamydomonas reinhardtii telomere (TTTTAGGG) n is found to be an exception to the general idea of forming a folded G-quadruplex by a few repeats in any telomeric sequence. Herein, using gel electrophoresis, UV thermal melting, UV thermal difference spectra (TDS), circular dichroism, and fluorescence and NMR spectroscopy. We demonstrated that the double repeat of the C. reinhardtii telomere (TTTTAGGG)2 (Chlm2) adopts an intramolecular non-conventional triplex structure in Na + solution. We report that the co-existence of reverse Hoogsteen (G·G) and Wobble base pairing (G·T) stabilizes the triplex structure. To the best of our knowledge, such a non-conventional triplex structure formed by any telomeric sequence has not been reported to date.